2018
DOI: 10.1038/s41565-018-0095-1
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: 2D MoS2 as an efficient protective layer for lithium metal anodes in high-performance Li–S batteries

Abstract: In the version of this Article originally published, a technical error in typesetting led to the traces in Fig. 3a being trimmed and made to overlap. The figure has now been corrected with the traces as supplied by the authors; the original and corrected Fig. 3a are shown below. Also, in the last paragraph of the section "Mechanistic study on Li diffusion in MoS" the authors incorrectly included the term 'high-concentration' in the text "the Li diffusion will be dominated by high-concentration Li migration on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…In contrast, AFH-10, AFH-25, and AFH-55 symmetrical cells show two semicircles. The first semicircle in the higher frequency range indicates the interfacial resistance of the artificial SEI or resistance of Li-ion flux through an artificial SEI, and the second semicircle in the lower frequency range indicates the R ct between the artificial SEI and the electrolyte 19,33,3639 . The lower R ct of AFH-10, AFH-25, and AFH-55 symmetrical cells can be attributed to the better electrolyte wettability of the artificial SEI, the effective control of side reactions, and the stabilized SEI 35,40,41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, AFH-10, AFH-25, and AFH-55 symmetrical cells show two semicircles. The first semicircle in the higher frequency range indicates the interfacial resistance of the artificial SEI or resistance of Li-ion flux through an artificial SEI, and the second semicircle in the lower frequency range indicates the R ct between the artificial SEI and the electrolyte 19,33,3639 . The lower R ct of AFH-10, AFH-25, and AFH-55 symmetrical cells can be attributed to the better electrolyte wettability of the artificial SEI, the effective control of side reactions, and the stabilized SEI 35,40,41 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the sharp capacity decay in bare Li/NMC111 is attributed to the failure of the conductive framework in the anode induced by the highly resistive, fragile, and unstable SEI formation, and dead Li covering Li anode 24 . The formation of unstable SEI, loss of Li, and electrolyte consumption due to the high surface area of Li dendrites cause the capacity fading and low CE in the bare Li devices 36 . Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The semicircle in the higher‐frequency range (Figure b) gives the interfacial resistance of an artificial layer or resistance of Li‐ion flux through an artificial graphite–SiO 2 bilayer. The semicircle in the lower‐frequency range (Figure b) gives the charge transfer resistance R ct at the interface between graphite–SiO 2 bilayer and the electrolyte 2a,14b,30,35,38,39. At fresh condition, the bare Li and graphite–SiO 2 Li symmetrical cells show charge transfer resistance R ct values of 588.60 and 124.40, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The migrated Li atoms into the atomically layered structure of MoS 2 reduce interfacial resistance and increase the flow of Li + to and from the Li metal anode. [31] The layered structure of MoS 2 not only improves the ionic conductivity and Li + transport but also retaining the polysulfide anions due to the negatively charged nanochannels. Recently, Hao et al [32] and Pan et al [33] reported ionselective membranes for LiÀ S batteries containing negatively charged nanochannels which give rise to the flow of Li + and blocking the polysulfide within the cathode premises.…”
Section: Introductionmentioning
confidence: 99%
“…The MoS 2 also enhances the Li + transport and conductivity owing to its atomically layered structure with negatively charged nanochannels. The migrated Li atoms into the atomically layered structure of MoS 2 reduce interfacial resistance and increase the flow of Li + to and from the Li metal anode . The layered structure of MoS 2 not only improves the ionic conductivity and Li+ transport but also retaining the polysulfide anions due to the negatively charged nanochannels.…”
Section: Introductionmentioning
confidence: 99%